Education in obstetrical ultrasound – an important factor for increasing the prenatal detection of congenital heart disease. (18th April 2013) - Asplin, Nina; Dellgren, Annika; Conner, Peter
Abstract: Objective: To evaluate the effects of postgraduate education in obstetrical ultrasound on the prenatal detection rate of congenital heart disease. Setting: Tertiary care center. Population: Experienced and less experienced midwives performing ultrasound scans. Methods: Number of fetuses and live‐born children with severe congenital heart malformations were extracted from patient records. The detection rates of experienced and less experienced midwives were compared following a postgraduate training program in obstetrical ultrasound. Main outcome measures: The prenatal detection rate of complex congenital heart malformations. Results: The prenatal detection rate for the entire unit increased significantly during the study period (32 vs. 69%, p  < 0.05). Following education, we observed a significant increase in detection rates (21 vs. 67%, p  < 0.01) among experienced midwives. In the group of less experienced midwives, we found a positive effect of training with considerably higher detection rates compared with results achieved by their more experienced colleagues before the program (40 vs. 21%). Conclusion: There is a clear improvement in the prenatal detection rates of complex heart malformations following a postgraduate education in obstetrical ultrasound. Similar training should be offered to both midwives and doctors performing routine scans to increase the standards of antenatal screening for congenital heart disease.